On the interrelationships between Iraqi EFL learners’ classroom environment, foreign language classroom anxiety and willingness to communicate: A SEM approach - Alyaa Abdulkareem Obaid; Mitra zeraatpishe; Akram Faravani (English Language Teaching Educational Journal, 2022)
Different factors play their roles in communication especially when the concern is a foreign language such as classroom environment, foreign language classroom anxiety and willingness to communicate. The purpose of the present study is to investigate the relationship among EFL Iraqi learner’s classroom environment, foreign language classroom anxiety and willingness to communicate. First, from among the available 260 English university students at Babylon university, 204 EFL intermediate language learners who studied English language were selected. The selection was based on their score in Cambridge Quick Placement Test 2004(QPT). The participants, then filled three questionnaires of anxiety, classroom environment, and willingness to communicate. The three questionnaires were filled out by the participants.  To consider the extent of the interrelationships among classroom environment, willingness to communicate and speaking anxiety, a model of associations among them was proposed. To analyze the obtained data, structural equation modelling (SEM) was used and the model was probed using AMOS. Results of SEM indicated a complete fit and significant interrelationship among the variables were found. The findings have several implications for EFL teachers and learners.